Epidemiology of candidemia in Shiraz, southern Iran: A prospective multicenter study (2016–2018). (21st July 2020) - Arastehfar, Amir; Yazdanpanah, Samira; Bakhtiari, Mina; Fang, Wenjie; Pan, Weihua; Mahmoudi, Shahram; Pakshir, Keyvan; Daneshnia, Farnaz; Boekhout, Teun; Ilkit, Macit; Perlin, David S; Zomorodian, Kamiar; et al.
Abstract: Systematic candidemia studies, especially in southern Iran, are scarce. In the current prospective study, we investigated candidemia in three major healthcare centers of Shiraz, the largest city in southern Iran. Yeast isolates from blood and other sterile body fluids were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and subjected to antifungal susceptibility testing (AFST) using the broth microdilution method. Clinical data were retrieved from patients' medical records. In total, 113 yeast isolates were recovered from 109 patients, over 60% of whom received fluconazole. Antifungal drugs were prescribed without considering species identification or AFST. The all-cause mortality rate was 28%. Almost 30% of the patients were from intensive care units (ICUs). Candida albicans (56/113; 49.5%) was the most prevalent species followed by C. glabrata (26/113; 23%), C. parapsilosis (13/113; 11.5%), C. tropicalis (7/113; 6.2%), and C. dubliniensis (5/113; 4.4%). Only five isolates showed antifungal resistance or decreased susceptibility to fluconazole: one C. orthopsilosis isolate from an azole-naïve patient and two C. glabrata, one C. albicans, and one C. dubliniensis isolates from patients treated with azoles, who developed therapeutic failure against azoles later. Our results revealed a low level of antifungal resistance but a notable rate of azole therapeutic failure among patients with candidemia due to non- albicans Candida species, which threaten the efficacy of fluconazole, the most widely used antifungal in southern regions of Iran. Candidemia studies should not be confined to ICUs and treatment should be administered based on species identification and AFST results. Lay Summary: Landscape of candidemia is blurred in Iran, and only two studies from Tehran have extensively explored the epidemiology of candidemia. However, candidemia data from the other regions are notoriously scarce, which precludes from reaching a consensus regarding species distribution, the burden of antifungal resistance, and the clinical features of infected patients. Therefore, we conducted the current prospective candidemia study in Shiraz, one of the largest cities located in the south of Iran, from April 2016 to April 2018. More than 63% of the candidemia infections were treated by fluconazole and species identification and antifungal susceptibility testing were not used for decision making regarding the choice of antifungal treatment. Approximately 70% of the candidemia cases occurred in the wards outside of the ICUs. Candida albicans, C. glabrata, C. parapsilosis, C. tropicalis, and C. dubliniensis were the five leading causative agents of candidemia. Antifungal resistance was rare and fluconazole resistance and/or non-wild type phenotypes were noticed in five isolates, only one was C. albicans and the rest were non- albicans Candida (NAC) species, including C. glabrata, C. dubliniensis, and C. orthopsilosis . Except for C. orthopsilosis, which was isolated from an azole-naïve patient, the rest of isolates were recovered from patients treated with azoles and all showed therapeutic failure to azoles. Collectively, our data will complete the candidemia picture in Iran and show that, although the level of resistance was rare, the therapeutic failure was notable among NAC species, which threatens the efficacy of fluconazole, the most widely used antifungal in Southern regions of Iran. Moreover, we showed that candidemia is poorly managed in Iran since species identification tools along with antifungal susceptibility testing were not used to select appropriate antifungal treatment.